Cogging torque reduction of segmented HEFSM using combined technique of notching and chamfering for performance improvement - Asadullah, Asadullah (2019)
Cogging torque is one of the factors which affect the motor in terms of vibration and non-audible noise that become serious issue in flux switching machines. It is mandatory for every motor to have low cogging torque because having low cogging torque enhancing the control based on positioning of the motor in electric vehicle drive application. This project focus on reducing the cogging torque of segmented rotor HEFSM having 24S-8P using various rotor techniques configuration such as notching (NOT) and chamfering (C.H), were examined. Then a new technique has been proposed and compared using combination of NOT and C.H for reduction of cogging torque. The new proposed design configuration has been executed using 2D commercial JMAG version 15.1 at no load and load conditions for analysing the best results. Initially techniques based on NOT and C.H has reduced the cogging torque by 46% and 57% respectively of the original value of 9.5Nm. Then a new proposed technique of combination of NOT and C.H reduced almost by 60% of the initial result simultaneously. This result is considered as the best reduced technique for reduction of cogging torque of segmented HEFSM. The performance of HEFSM segmented rotor 24S-8P has been increased by using “local optimization method” based on parameter sensitivity. The total performance torque is achieved almost 55% more than the initial torque 11.07Nm. The combined technique of NOT and C.H has successfully reduced the cogging torque which improves the motor performance in terms of acoustic noise and vibration.